2012
DOI: 10.1017/s1041610212000245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of suicidal thought and self-destructive behavior among an elderly hospital population in Iran

Abstract: Hospitalized, physically ill elderly patients have high rates of suicidal ideation and self-destructive behavior and these vary according to psychosocial and clinical factors. The general hospital is therefore a potential site for the recognition of suicidal individuals and implementation of proximal suicide prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
0
26
2
1
Order By: Relevance
“…Among the seven studies investigating non-fatal SIB, results were mixed for studies using bivariate analysis, with three 32,46,54 showing positive and three 32,41,46 null associations. When multivariate analysis was performed, only one Iranian study 54 reported a positive association between unemployment rates and suicide attempts (OR=2•54, 95% CI 1•08-5•98).…”
Section: Unemploymentmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the seven studies investigating non-fatal SIB, results were mixed for studies using bivariate analysis, with three 32,46,54 showing positive and three 32,41,46 null associations. When multivariate analysis was performed, only one Iranian study 54 reported a positive association between unemployment rates and suicide attempts (OR=2•54, 95% CI 1•08-5•98).…”
Section: Unemploymentmentioning
confidence: 99%
“…We assessed 29 (78%) studies to be of high [30][31][32][33][34][35][36][37][38][39][40][41][42][43] or acceptable [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] quality (Table 3). Eight studies [59][60][61][62][63][64][65][66] were of low quality due to problems with risk of bias: performance, attrition and detection bias (interrupted-time series); selection bias, unclear case definitions, detection bias, lack of adjustment for confounding factors (case-control studies); detection bias, lack of adjustment for confounding factors (cross sectional and ecological studies).…”
Section: <Figure 1> <Table 2>mentioning
confidence: 99%
See 2 more Smart Citations
“…None of the variables, education and marital status, were identified as being effective in the incidence of harmful behaviors. But a study conducted at Shiraz University of Medical Sciences, Iran has shown that the incidence of harmful behaviors is more common in people with lower educational levels (16). Our study had been performed on those who lacked comorbid axis I psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%